Partnership, power and politics : feminist perceptions of midwifery practice : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy - Fleming, Valerie E. M. (Massey University, 1995)
This thesis provides an interpretative critique of the partnership of a group of independent midwives and their clients in urban New Zealand. A theoretical basis grounded in the principles of feminism but incorporating aspects of critical social science and postmodernism underpins both the methodological approach and analysis of data. The major concepts of subjectivity, power/knowledge and praxis have been utilised as tools for analysis of data, primarily collected through semi-structured interviews. Results of this study showed that while the partnership of midwife and client became increasingly intense as each pregnancy progressed, and participants reported that it was important that clients knew their midwives prior to labour, feelings of intimacy and trust only emerged during and after labour. Midwives in this study were aware of the power they had and the potential for abuse of this power despite the notion of partnership. It is argued that the reflexive processes involved with this research have motivated the participants to become aware that their knowledge and actions are shaped by aspects of the dominant social order. While collective political action by midwives and clients with a view to overcoming this was not fully demonstrated in this study, it is suggested that by engaging in this research there may be ongoing emancipatory effects for the participants and other midwives.
Keywords: Midwifery; Midwife client partnership; Midwives